2021
DOI: 10.29303/ekonobis.v7i2.74
|View full text |Cite
|
Sign up to set email alerts
|

Survey Pekerja Sektor informal Dan Sektor Formal Era Revolusi Industri di Kota Mataram

Abstract: Tujuan penelitian adalah untuk menganalisis Pendapatan dan Tingkat kesejahteraan Pekerja sektor Informal dan Formal di Kota Mataram pada era Covid -19. Metode penelitian dilakukan dengan cara survey dengan mengambil sampel sebanyak 90 orang responden, dan penentuan responden ditentukan secara accidental dengan melihat karakteristik dari kedua pekerja tersebut.Karakteristik dari pekerja informal dan formal sebagian besar berjualan ditempat-tempat keramaian yang padat penduduk dan pengunjung di wilayah kota Mata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Indonesia is one country with the increasing number of unemployment, while the market figure is decreasing". [13]. Besides, figure 6 shows that the average workers of the online informal sector graduated from Senior high school levels (SMA/MA/SMK), with 96%.…”
Section: Disruptive Innovation Of the Online Informal Sector In Palem...mentioning
confidence: 98%
“…Indonesia is one country with the increasing number of unemployment, while the market figure is decreasing". [13]. Besides, figure 6 shows that the average workers of the online informal sector graduated from Senior high school levels (SMA/MA/SMK), with 96%.…”
Section: Disruptive Innovation Of the Online Informal Sector In Palem...mentioning
confidence: 98%
“…Pendapatan di sektor informal umumnya 6dak stabil dan memiliki risiko yang cukup 6nggi, sehingga pendapatan yang diperoleh sebagian besar digunakan untuk pemenuhan kebutuhan sehari-hari. (Lestari, 2023); (Prasetya & Hidayat, 2020); (Sujadi, 2021) dalam ar6kelnya menyatakan bahwa ada ke6mpangan pendapatan di sektor informal dibandingkan dengan nilai UMP, begitu pula jika dibandingkan pendapatan pekerja informal dengan ketersediaan beras, masuk dalam golongan miskin. Pendapatan yang 6dak stabil mempengaruhi keberadaan petani untuk berbelanja modal bagi kelangsungan usahatani, seper6 benih yang berkualitas, peralatan pertanian dan akses terbatas terhadap pupuk anorganik.…”
Section: Pendahuluanunclassified
“…The formal sector is a business sector that has received permission from the government or authorized officials in a region where the business has been registered with a government agency and is recognized by the state. Satarudin et al, (2021) revealed that the formal sector is a field or field of business that receives permission from authorized officials and is registered with a government office.…”
Section: Formal Sectormentioning
confidence: 99%
“…The formal sector and informal sector describe how economic activities are organized and carried out by society. The formal business sector is a field or field of business that receives permission from authorized officials and is registered with a government office (Satarudin et al, 2021). Meanwhile, the informal business sector is a business that is unofficial or unorganized, irregular, and legal but not registered (Sakri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%